Medical Activities of the Southern Baptist Convention in Modern Times: Focusing on Sida Hospital in Wuzhou, Guangxi - LIU Meixin, (Journal of Research for Christianity in China (JRCC), 2025)
Taking Guangxi Wuzhou Sida Hospital as a case study, this research examines its arduous and tortuous development process. Although the hospital was founded with the original intention of serving the public, its role and influence have historically expanded beyond religious boundaries. Through analyzing the hospital's operations and management, its impact on the local community becomes evident.
Keywords: Wuzhou Sida Hospital Spreading the Gospel Operation and Management Local Society